PRAGMATISME KADERISASI INTERNAL DPP PARTAI GOLKAR ERA REFORMASI (STUDI KASUS DI DPP PARTAI GOLKAR) - Ghiffary Asy Syaukani; Fitriyah . (Journal of Politic and Government Studies, 2020)
This research is to find out why pragmatism occurs in internal regeneration in the Golkar Party DPP which is the object of this research in carrying out the party's cadre. The method used in this research is descriptive qualitative method, which is trying to describe and interpret what happened. Based on the results found in the field research, it is explained that the pragmatism that occurs in the internal regeneration of the Golkar Party DPP is caused by many related factors, since the Election system in Indonesia uses the Open Proportional System, the Golkar Party tends to be pragmatic, ie, views its cadres and prospective cadres from how likely they are to be able to bring the Golkar Party won votes and influence from the community. In this case those who are considered pragmatically are classified as ADP (Activists, Blue Blood, and Entrepreneurs) These 3 groups are considered to be more beneficial to the Golkar Party than other cadres.Keywords: Political Parties, Recruitment, Cadreization